Cooking and Utilitarian Wares from a Water Crypt in Ancient Messene - Anastasia Yangaki (Rei Cretariae Romanae Fautorum Acta, 2024)
During excavations at ancient Messene (Peloponnese) a pottery assemblage was found dumped within a water crypt that constituted part of the sanctuary of Sarapis and Isis and had been used as a refuse pit after the abandonment of the complex following 365 AD. The assemblage comprises only cooking wares and utilitarian closed forms, together with few auxiliary clay objects. Three main fabrics make up the bulk of the ceramics and can be attributed to the local productions. Numerous examples of four main types of cooking pots have been revealed. Considering the deficiencies observed in the manufacture of most of these vessels and the fact that some of them are over-fired, it is argued that what has been excavated from the water crypt constitutes wasters rejected from a kiln-firing event in this particular area. Based on the evidence, this assemblage should be dated within the 5th century AD.